2023
DOI: 10.1080/13504509.2023.2167884
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Sustainable Development Goals into the strategy of higher education institutions

Abstract: Despite the relevance of the UN Sustainable Development Goals (SDGs) and the fact that universities may make valuable contributions towards their implementation, there is a paucity of international studies which may allow an assessment of their degree of engagement or their performance against the SDGs. This paper reports on an international study among a sample of 128 members of higher education institutions (HEIs) located in 28 countries, which aimed at ascertaining the extent to which the SDGs are being int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…Many actions have been implemented for an extended period, which positions them in a suitable stage of maturity. The institution's current major challenge is integrating sustainable development initiatives into an integrated, holistic system (Leal Filho et al, 2023). There are two main areas for improvement in achieving this goal.…”
Section: Resultsmentioning
confidence: 99%
“…Many actions have been implemented for an extended period, which positions them in a suitable stage of maturity. The institution's current major challenge is integrating sustainable development initiatives into an integrated, holistic system (Leal Filho et al, 2023). There are two main areas for improvement in achieving this goal.…”
Section: Resultsmentioning
confidence: 99%
“…La investigación de (Leal Filho, Simaens, et al, 2023) realizada IES de 28 países, identificó el hecho de que, mientras que muchas organizaciones son conscientes de la necesidad y la relevancia del desarrollo sostenible y lo consideran como parte de sus entornos institucionales, no se puede decir lo mismo de los ODS, cuyo nivel de énfasis es que muchas IES son comparativamente algo limitadas. Además, parece haber una escasez de oportunidades de capacitación centradas en los ODS, lo que podría equipar al personal universitario para manejar este tema.…”
Section: Estructuración Desde La Carrera Universitaria Para Potenciar...unclassified
“…The studies by Leal Filho et al (2023b) with HEI members in several countries revealed that, although many organizations are already aware of the importance of sustainable development and integrate it in their institutional mission and vision, the integration of SDGs in operational processes remains limited. Thus, although there has been some progress, the existence of barriers has delayed SDG implementation in higher education; these barriers include lack of training, financial and human resources, policies and government commitment (Aleixo et al , 2018b; Leal Filho et al , 2019; Serafini et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%